The Implementation of Cooperative Learning Method: Revitalizing the Learning Process of Islamic Religious Eduation - Wahyuni Eka Sandy; Agus Fakhruddin; Muhamad Parhan (Jurnal Educative: Journal of Educational Studies, 2024)
Good classroom management is the key to creating active learning in Islamic Religious Education (IRE) learning. Cooperative learning is an alternative method for teachers to revitalize IRE learning to be more enjoyable and increase student activity. The purpose of this study was to evaluate the impact of the cooperative learning method in increasing student activity in IRE learning in schools, especially at SMP Putra Pakuan Bogor. The research method used in this study was a descriptive qualitative approach with observation and interviews with teachers and students as data collection techniques. Data were analyzed using thematic analysis to identify core themes related to student activity in IRE learning. The results showed that the application of the cooperative learning method succeeded in increasing student activity in IRE learning in schools. By creating a fun learning environment, students become active participants in learning so that it has an impact on students in understanding the material more easily. From this study, the author recommends that teachers consistently apply the cooperative learning method in IRE learning to continue to increase student activity and understanding of the material being taught. Pengelolaan kelas yang baik menjadi kunci untuk menciptakan pembelajaran yang aktif dalam pembelajaran Pendidikan Agama Islam (PAI). Cooperative learning menjadi alternatif metode bagi guru untuk merevitalisasi pembelajaran PAI menjadi lebih menyenangkan dan meningkatkan keaktifan siswa. Tujuan penelitian ini adalah untuk mengevaluasi dampak metode pembelajaran cooperative learning dalam meningkatkan keaktifan siswa dalam Pembelajaran PAI di sekolah, khususnya di SMP Putra Pakuan Bogor. Metode penelitan yang digunakan pada penelitian ini yaitu menggunakan pendekatan kualitatif deskriptif dengan observasi dan wawancara terhadap guru dan siswa sebagai teknik pengumpulan data. Data dianalisis menggunakan analisis tematik untuk mengidentifikasi tema inti yang terkait dengan keaktifan siswa dalam pembelajaran PAI. Hasil penelitian menunjukkan bahwa penerapan metode cooperative learning berhasil meningkatkan keaktifan siswa dalam pembelajaran PAI di sekolah. Dengan menciptakan lingkungan pembelajaran yang menyenangkan membuat siswa menjadi aktif berpartisipasi dalam pembelajaran sehingga hal tersebut berdampak pada siswa dalam memahami materi menjadi lebih mudah. Dari penelitian ini penulis merekomendasikan agar guru secara konsisten menerapkan metode cooperative learning dalam pembelajaran PAI untuk terus meningkatkan keaktifan dan pemahaman siswa terhadap materi yang diajarkan.